c-Jun regulates phosphoinositide-dependent kinase 1 transcription: implication for Akt and protein kinase C activities and melanoma tumorigenesis - Lopez Bergami, Pablo Roberto (2010)
utations in N-RAS and B-RAF, which commonly occur in melanomas, result in constitutive activation of the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated protein kinase (ERK) signaling. Active ERK increases expression and activity of the c-Jun transcription factor, linking ERK and Jun N-terminal kinase (JNK) cascades. Here, we show that c-Jun regulates transcription of phosphoinositide-dependent kinase 1 (PDK1) with a concomitant impact on Akt and protein kinase C (PKC) activity and related substrates. Inhibition of c-Jun reduces PDK1 expression and attenuates Akt and PKC activity, which can be restored by exogenous PDK1. c-Jun regulation of PDK1 in melanoma contributes to growth rate and the ability to form tumors in mice. Correspondingly, increased levels of c-Jun in melanoma cell lines coincide with up-regulation of PDK1 and phosphorylation of PKC and Akt. The identification of c-Jun as a transcriptional regulator of PDK1 expression highlights key mechanisms underlying c-Jun oncogenic activity, and provides new insight into the nature of up-regulated Akt and PKC in melanoma.